الطريقة الرحمانية وأحداث الثامن ماي 1945 - محجوب, حورية (University of Eloued جامعة الوادي, 2022)
تعد حوادث ثامن ماي 1945 مرحلة فاصلة في تاريخ الجزائر الحديث والمعاصر، إذ مهدت لعهد جديد وملحمة خالدة، حيث تعتبرها الكتابات التاريخية الشرارة الأولى لانطلاق ثورة الفاتح نوفمبر 1954م، فقد أيقظت هذه الحوادث النفوس، وتيقن الشعب الجزائري أن ما أخذ بالقوة لا يسترجع إلا بالقوة. مما جعل الأحرار يتبنونها ويساهمون في إيضاحها، ومنهم الشباب القاسمي، الذي تفرد من خلال جريدة الروح بكتابة مقالات متعددة بمناسبة المجازر The events of the eighth of May 1945 are considered the memory of the history, as they paved the way for a new era and an immortal epic. Historical writings consider it the first spark for the start of the November liberation revolution. Only these events awoke the souls, and the people realized through them that what was taken by force can only be recovered by force. Among those who contributed to clarify and highligh the events of May 8, 1945: Al Qasimi Youth, whowrote several articles, through Al-Rouh newspaper, on the occasion of the third anniversary of the massacres of the13/5/1948.